Application of GA in Furniture Modeling Style Design - Heng Yu; Chunjing Liu (Journal of Function Spaces)
With the rapid development of the national economy, the construction industry is unprecedentedly active and has made great achievements. However, most traditional structural design is based on the personal experience of designers. In order to improve the production efficiency of furniture, it is necessary to optimize it. Since the evaluation criteria mainly depend on people’s subjective thoughts, it is difficult to describe the individual’s adaptive function. In this paper, an interactive innovation evolution system based on evolutionary algorithm is proposed. Taking full advantage of the evolution function of genetic algorithm and the modeling advantages of ACIS platform, a prototype innovation evolution system is developed based on ACIS/hoops platform with the genetic algorithm based on tree structure as the innovation support, which can help designers complete the innovation modeling design. The results show that the total processing time of the sorting scheme obtained by this algorithm is reduced by 2475.2 s, the production efficiency is increased by 20.6%, and the job waiting time is reduced by 15079.2 s. The results show that the algorithm is feasible and effective in solving the furniture production scheduling problem. The furniture production scheduling scheme solved by genetic algorithm can provide certain reference value for production personnel to formulate production scheduling scheme and improve production efficiency.